2021
DOI: 10.33603/perspective.v9i1.5150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Kiky Saputri�s Roasting as Critiques Towards Politicians

Abstract: Recently, roasting as one of the stand-up comedy techniques has become an entertainment favored by Indonesian people. Roasting is a series of jokes that aims to comment on a specific person. This study will use data from one of the videos on YouTube showing Kiky Saputri roasting four ministers, namely Hanif Dhakari, Rudiantara, Retno Marsudi, and Susi Pudjiastuti. This study will use the theory of humor and satire to find out the meaning of Kiky's roasting material. This study shows that each roasting word giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Kiky Saputri adalah salah satu tokoh yang terkenal akan roasting komedi terutama roasting kepada pejabat di Indonesia. Wacana kritik sosial yang disampaikan Kiky Saputri berdasarkan berita-berita dan fenomena sosial yang terkait dengan figur pejabat politik (Sihombing, 2021) Tujuan dari penelitian ini adalah untuk memahami bagaimana Kiky Saputri mengkritik isu sosial melalui analisis wacana kritis Model Teun A. Van Dijk.…”
Section: Pendahuluanunclassified
“…Kiky Saputri adalah salah satu tokoh yang terkenal akan roasting komedi terutama roasting kepada pejabat di Indonesia. Wacana kritik sosial yang disampaikan Kiky Saputri berdasarkan berita-berita dan fenomena sosial yang terkait dengan figur pejabat politik (Sihombing, 2021) Tujuan dari penelitian ini adalah untuk memahami bagaimana Kiky Saputri mengkritik isu sosial melalui analisis wacana kritis Model Teun A. Van Dijk.…”
Section: Pendahuluanunclassified
“…Dalam penelitian Alam (Alam, 2017) misalnya, menyebutkan bahwa pada ajang perlombaan Stand Up Comedy Indonesia Season 4 tahun 2014, berbagai materi yang dibawakan banyak mengarah pada kritik pemerintah, praktik politik, dan hubungan sosial yang tidak hanya dibawakan dengan kata-kata, namun juga dengan gerak tubuh (act-out), karakter yang dimainkan (persona), dan cara penyampaian (delivery). Bahkan, pada 2019, 4 menteri dihadirkan dan menjadi bahan kritikan (roasting) dari salah satu comic, yaitu Kiki Saputry (Sihombing et al, 2021). Roasting tersebut terkait kinerja mereka selama menjadi Menteri atau hobi-hobi mereka.…”
Section: Hubungan Humor Dan Agama DI Indonesiaunclassified
“…Despite its uniqueness, little research has been done to analyze the art of roasting comedy (Lilaifi, 2019;Sihombing et al, 2021). In her research, Lilaifi (2019) analyzed the language play by Ridwan Remin, who is well-known for being a 'king' roasting.…”
mentioning
confidence: 99%
“…Lastly, she also found out that in his speech, it is shown that Ridwan Remin's language play functioned mainly as humor. Secondly, Sihombing et al (2021) studied several videos of roasting comedy by Kiky Saputri. This study used Kiky Saputri's video when she acted as the "roastmaster" to several ministers such as Susi Pudjiastuti, Rudiantara, Retno Marsudi, and Hanif Dhakari.…”
mentioning
confidence: 99%